Genetic variability of Physalis ixocarpa and P. philadelphica from physicochemical fruit traits - Santos, Keylla Souza dos; Passos, Adriana Rodrigues; Silva, Luiz Cláudio Costa; Silva, Alismário Leite da; Tanan, Tamara Torres (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to estimate the genetic parameters and genetic divergence of two species of Physalis based on fruit traits, as well as the correlations between these traits. The experiment was carried out in a randomized complete block, with three treatments (P. philadelphica and the green and purple varieties of P. ixocarpa), and six replicates. The following traits were evaluated: average fruit mass (AFM), soluble solids (SS), longitudinal fruit diameter (LFD), transversal fruit diameter (TFD), total fruit mass (TFM), number of fruit per plant (NF), reducing sugars (RS), and total sugars (TS). Genetic divergence was estimated by Tocher’s and the UPGMA methods. There was genetic divergence between the Physalis species, with a higher contribution of AFM, LFD, and TFD, mainly by Tocher’s method. A positive correlation was observed between AFM x LFD, AFM x TFD, and LFD x TFD, and a negative correlations between LFD x TFM, TFD x TFM, and NF x RS. The species were discriminated by total sugars. The AFM, LFD, TFD, and TS traits show significant genetic variation and high values of heritability; therefore, they are suitable targets for the genetic breeding of the evaluated Physalis species.